Новые виды рода Melolonthinimermis Art., (Nematoda, Mermitidae) с уточнением диагноза рода - Артюховский, А.К. (Вестник зоологии, 1979)
Three new species Melolonthinimermis karpatica sp. n., M popovi sp. n. and M. bukovinae, sp. n. are described and their drawings are given. Diagnosis of genus Melolonthi nimermis is specified, and the key of species of this genus is given.